Diagnostics of Piezoelectric Bending Actuators Subjected to Varying Operating Conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Hemsel, Tobias; Sextro, Walter (Electronics)
In applications of piezoelectric actuators and sensors, the dependability and particularly the reliability throughout their lifetime are vital to manufacturers and end-users and are enabled through condition-monitoring approaches. Existing approaches often utilize impedance measurements over a range of frequencies or velocity measurements and require additional equipment or sensors, such as a laser Doppler vibrometer. Furthermore, the non-negligible effects of varying operating conditions are often unconsidered. To minimize the need for additional sensors while maintaining the dependability of piezoelectric bending actuators irrespective of varying operating conditions, an online diagnostics approach is proposed. To this end, time- and frequency-domain features are extracted from monitored current signals to reflect hairline crack development in bending actuators. For validation of applicability, the presented analysis method was evaluated on piezoelectric bending actuators subjected to accelerated lifetime tests at varying voltage amplitudes and under external damping conditions. In the presence of a crack and due to a diminished stiffness, the resonance frequency decreases and the root-mean-square amplitude of the current signal simultaneously abruptly drops during the lifetime tests. Furthermore, the piezoelectric crack surfaces clapping is reflected in higher harmonics of the current signal. Thus, time-domain features and harmonics of the current signals are sufficient to diagnose hairline cracks in the actuators.
Keywords: piezoelectric transducer; self-sensing; fault detection; diagnostics; hairline crack; condition monitoring

Transferability of a discrepancy model for the dynamics of electromagnetic oscillating circuits - Wohlleben, Meike Claudia; Muth, Lars; Peitz, Sebastian; Sextro, Walter (Proceedings in Applied Mathematics and Mechanics)
Modelling of dynamic systems plays an important role in many engineering disciplines. Two different approaches are physical modelling and data‐driven modelling, both of which have their respective advantages and disadvantages. By combining these two approaches, hybrid models can be created in which the respective disadvantages are mitigated, with discrepancy models being a particular subclass. Here, the basic system behaviour is described physically, that is, in the form of differential equations. Inaccuracies resulting from insufficient modelling or numerics lead to a discrepancy between the measurements and the model, which can be compensated by a data‐driven error correction term. Since discrepancy methods still require a large amount of measurement data, this paper investigates the extent to which a single discrepancy model can be trained for a physical model with additional parameter dependencies without the need for retraining. As an example, a damped electromagnetic oscillating circuit is used. The physical model is realised by a differential equation describing the electric current, considering only inductance and capacitance; dissipation due to resistance is neglected. This creates a discrepancy between measurement and model, which is corrected by a data‐driven model. In the experiments, the inductance and the capacity are varied. It is found that the same data‐driven model can only be used if additional parametric dependencies in the data‐driven term are considered as well.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Expert-Informed Hierarchical Diagnostics of Multiple Fault Modes of a Spacecraft Propulsion System - Aimiyekagbon, Osarenren Kennedy; Löwen, Alexander; Bender, Amelie; Muth, Lars; Sextro, Walter (Proceedings of the Asia Pacific Conference of the PHM Society 2023)
This paper presents a comprehensive study on diagnosing a spacecraft propulsion system utilizing data provided by the Prognostics and Health Management (PHM) society, specifically obtained as part of the Asia-Pacific PHM conference’s data challenge 2023. The objective of the challenge is to identify and diagnose known faults as well as unknown anomalies in the spacecraft’s propulsion system, which is critical for ensuring the spacecraft’s proper functionality and safety. To address this challenge, the proposed method follows a systematic approach of feature extraction, feature selection, and model development. The models employed in this study are kMeans clustering and decision trees combined to ensembles, enriched with expert knowledge. With the method presented, our team was capable of reaching high accuracy in identifying anomalies as well as diagnosing faults, resulting in attaining the seventh place with a score of 93.08 %.
Keywords: PHM; Fault Diagnostics; Multiple Fault Modes; Expert-Informed Diagnostics; Anomaly Detection

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Experimental Investigation of Bond Formation and Wire Deformation in the Ultrasonic Wire Bonding Process - Scheidemann, Claus; Hagedorn, Oliver Ernst Caspar; Hemsel, Tobias; Sextro, Walter

Einfluss der Radhubkinematik auf den Reifenverschleiß - Schütte, Jan; Sextro, Walter (20. VDI-Fachtagung Reifen - Fahrwerk - Fahrbahn)

Generation of a Reduced, Representative, Virtual Test Drive for Fast Evaluation of Tire Wear by Clustering of Driving Data - Muth, Lars; Noll, Christian; Sextro, Walter (Advances in Dynamics of Vehicles on Roads and Tracks II - Proceedings of the 27th Symposium of the International Association of Vehicle System Dynamics, IAVSD 2021)
Tire and road wear are a major source of emissions of nonexhaust particulate matter (PM) and make up the largest share of microplastics in the environment. To reduce tire wear through numerical optimization of a vehicle's suspension system, fast simulations of the representative usage of a vehicle are needed. Therefore, this contribution evaluates if instead of a full simulation of a representative test drive, only specific driving maneuvers resulting from a clustering of the driving data can be used to predict tire wear. As a measure for tire wear, the friction work between tire and road is calculated. It is shown that enough clusters result in negligible deviations between the total friction work of the full simulation and the cluster simulations as well as between the distributions of the friction work over the tire width. The calculation time can be reduced to about 1% of the full simulation.
Keywords: Tire Wear; Vehicle Dynamics; Clustering; Virtual Test

Development of a Hybrid Modeling Methodology for Oscillating Systems with Friction - Wohlleben, Meike Claudia; Bender, Amelie; Peitz, Sebastian; Sextro, Walter (Machine Learning, Optimization, and Data Science)

Experimental Investigation of the Influence of different Bond Tool Grooves on the Bond Quality for Ultrasonic Thick Wire Bonding - Hagedorn, Oliver Ernst Caspar; Broll, Marian; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (CIPS 2022 - 12th International Conference on Integrated Power Electronics Systems)
To achieve optimum bond results at ultrasonic bonding thick copper wire on sensitive components is quite challenging. Bearing in mind that high normal force and ultrasonic power are needed for bond quality but as well increase stress and finally failure risk of the substrate, methods should be found to achieve high bond quality even at lower bond parameters. Therefore, bond experiments with different bond tool grove geometries have been conducted for copper and aluminum wire on direct copper bonded (DCB) substrates to investigate the impact of geometric parameters on bond formation and bond quality. The wire material depending impact of geometry changes on the bond formation and deformation was quantified. Additionally, a bonding parameter design of experiments (DOE) has been conducted for the reference and the most promising groove geometry. Higher shear values were achieved at reduced vertical tool displacement for most bonding parameter combinations, compared to the reference tool. This behavior allows for reducing ultrasonic power to obtain equal shear values; consequently, mechanical stresses in the interface decrease. This could potentially reduce the risk of chip damage and thus yield loss.

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Condition Monitor)

Experimental Investigation of Multidimensional Ultrasonic Heavy Wire Bonding - Scheidemann, Claus; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (2022 IEEE 9th Electronics System-Integration Technology Conference (ESTC))
ue to the constantly growing energy demand of power electronics and the need to reduce the size of electronic components like power modules for e-mobility, new challenges arise for ultrasonic wire bonding: the electrical connection must endure higher thermal and mechanical stress while the connecting partners become more sensitive or require more energy to get bonded. Past investigations have shown already that multi-dimensional ultrasonic bonding and welding yield the same or even better bond quality while reducing the load on the components. This contribution is intended to show whether multidi-mensional thick wire bonding is a promising concept to over-come the new challenges. The focus is on experimental investi-gations of different bond tool trajectories in ultrasonic wire bonding of aluminum and copper wire on DCB's and chips. The bond quality is analyzed by shear tests, microsections and, in the case of aluminum bonding, by a new machine learning method for an objective automated evaluation of the sheared area.

Patent DE 10 2017 000 926 B4: Gerät mit wenigstens einem elastisch verformbaren Bauteil, insbesondere einem Gummi-Metall-Lager und mit einer Einrichtung zur Feststellung des Beginns einer verschleißbedingten Bauteil-Restnutzungsdauer, sowie Verfahren zur Bestimmung der Bauteil-Restnutzungsdauer. - Reinke, Kai; Bender, Amelie; Meyer, Tobias; Sextro, Walter; Kimotho, James Kuria
Die Erfindung betrifft ein Gerät mit wenigstens einem elastisch verformbaren Bauteil als Strukturteil und/oder Lagerteil, auf das im Betriebsverlauf von wechselnden Betriebszuständen abhängige, unterschiedliche Verformungskräfte einwirken, die zu einem die Bauteilnutzungsdauer begrenzenden Bauteilverschleiß führen, und mit einer Einrichtung zur Bestimmung der Bauteilnutzungsdauer und einer verschleißbedingten Bauteil-Restnutzungsdauer. Erfindungsgemäß wird ein sich zeitversetzt wiederholender, jeweils gleicher Betriebszustand vorbestimmt, dem eine jeweils gleiche, periodisch wirkende Verformungskraft zugeordnet ist, durch die das elastisch verformbare Bauteilmaterial periodisch verformt wird, wobei durch Walkarbeit ein Energieeintrag mit einem messbaren Temperaturanstieg im Vergleich zu einer Umgebungstemperatur erfolgt und wobei der jeweilige Temperaturanstieg als Kenngröße im Verlauf einer Bauteilnutzungsdauer entsprechend einer abnehmenden Bauteilsteifigkeit größer wird. Ein solcher vorbestimmter Betriebszustand wird jeweils von einer Messund Auswerteeinheit erkannt und ein Messvorgang durch ein Startsignal selbsttätig gestartet, wobei mit wenigstens einem bauteilzugeordneten Temperatursensor, der aktuelle Temperaturanstieg im Vergleich zur Umgebungstemperatur als Kenngröße für eine aktuelle Bauteilsteifigkeit gemessen und jeweils in einer Messkurve gespeichert und verglichen wird.

Modellbasierte Ermittlung optimaler Prozessparameter für neuartige Ultraschallbondverbindungen - Scheidemann, Claus; Hemsel, Tobias; Sextro, Walter

Extraktion und Selektion geeigneter Merkmale für die Restlebensdauerprognose von technischen Systemen trotz aleatorischen Unsicherheiten - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (VDI-Berichte 2391)
Aufgrund der Fortschritte der Digitalisierung finden Systeme zur Zustandsüberwachung vermehrt Einsatz in der Industrie, um durch eine zustandsbasierte oder eine prädiktive Instandhaltung Vorteile, wie eine verbesserte Zuverlässigkeit und geringere Kosten zu erzielen. Dabei beruhen Zustandsüberwachungssysteme auf den folgenden Bausteinen: Sensorik, Datenvorverarbeitung, Merkmalsextraktion und -auswahl, Diagnose bzw. Prognose sowie einer Entscheidungsfindung basierend auf den Ergebnissen. Jeder dieser Bausteine erfordert individuelle Einstellungen, um ein geeignetes Zustandsüberwachungssystem für die jeweilige Anwendung zu entwickeln. Eine offene Fragestellung im Bereich der Zustandsüberwachung ergibt sich aufgrund der Unsicherheit der Zukunft, die sich in den zukünftigen Betriebs- und Umgebungsbedingungen zeigt. Diese Unsicherheit gilt es in allen Bausteinen zu berücksichtigen. Dieser Beitrag konzentriert sich auf den Baustein Merkmalsextraktion und -selektion, mit dem Ziel anhand geeigneter Merkmale eine Prognose der nutzbaren Restlebensdauer mit hoher Genauigkeit realisieren zu können. Daher werden geeignete Merkmale aus dem Zeitbereich und daraus abgeleitete Zustandsindikatoren für die Restlebensdauerprognose von technischen Systemen vorgestellt. Dabei sind Zustandsindikatoren Kenngrößen zur Beobachtung des Zustands der kritischen Systemkomponenten. Anhand dreier Anwendungsbeispiele wird ihre Eignung evaluiert. Dabei werden Daten aus Lebensdauerversuchen unter instationären Betriebs- und Umgebungsbedingungen ausgewertet. Die auftretenden Unsicherheiten der Zukunft werden somit berücksichtigt. Die Beispielsysteme beruhen auf Gummi-Metall-Elementen und Wälzlagern. Aus den generierten Ergebnissen lässt sich schließen, dass die Zustandsindikatoren aus der betrachteten Zeitreihen-Toolbox auch unter unbekannten Betriebs- und Umgebungsbedingungen robust sind.
Keywords: run-to-failure; rubber-metal element; bearing prognostics; non-stationary operating conditions; varying operating conditions; feature extraction; feature selection

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Hybrid Prediction Method for Remaining Useful Lifetime Estimation Considering Uncertainties - Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
Predictive Maintenance as a desirable maintenance strategy in industrial applications relies on suitable condition monitoring solutions to reduce costs and risks of the monitored technical systems. In general, those solutions utilize model-based or data-driven methods to diagnose the current state or predict future states of monitored technical systems. However, both methods have their advantages and drawbacks. Combining both methods can improve uncertainty consideration and accuracy. Different combination approaches of those hybrid methods exist to exploit synergy effects. The choice of an appropriate approach depends on different requirements and the goal behind the selection of a hybrid approach. In this work, the hybrid approach for estimating remaining useful lifetime takes potential uncertainties into account. Therefore, a data-driven estimation of new measurements is integrated within a model-based method. To consider uncertainties within the system, a differentiation between different system behavior is realized throughout diverse states of degradation. The developed hybrid prediction approach bases on a particle filtering method combined with a machine learning method, to estimate the remaining useful lifetime of technical systems. Particle filtering as a Monte Carlo simulation technique is suitable to map and propagate uncertainties. Moreover, it is a state-of-the-art model-based method for predicting remaining useful lifetime of technical systems. To integrate uncertainties a multi-model particle filtering approach is employed. In general, resampling as a part of the particle filtering approach has the potential to lead to an accurate prediction. However, in the case where no future measurements are available, it may increase the uncertainty of the prediction. By estimating new measurements, those uncertainties are reduced within the data-driven part of the approach. Hence, both parts of the hybrid approach strive to account for and reduce uncertainties. Rubber-metal-elements are employed as a use-case to evaluate the developed approach. Rubber-metal-elements, which are used to isolate vibrations in various systems, such as railways, trucks and wind turbines, show various uncertainties in their behavior and their degradation. Those uncertainties are caused by diverse inner and outer factors, such as manufacturing influences and operating conditions. By expert knowledge the influences are described, analyzed and if possible reduced. However, the remaining uncertainties are considered within the hybrid prediction method. Relative temperature is the selected measurand to describe the element’s degradation. In lifetime tests, it is measured as the difference between the element’s temperature and the ambient temperature. Thereby, the influence of the ambient temperature on the element’s temperature is taken into account. Those elements show three typical states of degradation that are identified within the temperature measurements. Depending on the particular state of degradation a new measurement is estimated within the hybrid approach to reduce potential uncertainties. Finally, the performance of the developed hybrid method is compared to a model-based method for estimating the remaining useful lifetime of the same elements. Suitable performance indices are implemented to underline the differences between the results.
Keywords: Hybrid prediction method; Multi-model particle filtering; Uncertainty quantification; RUL estimation

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Proceedings of the Seventeenth International Conference on Condition Monitoring and Asset Management (CM 2021))
Several methods, including order analysis, wavelet analysis and empirical mode decomposition have been proposed and successfully employed for the health state estimation of technical systems operating under varying conditions. However, where information such as the speed of rotating machinery, component specifications or other domain-specific information is unavailable, such methods are often infeasible. Thus, this paper investigates the application of classical time-domain features, features from the medical field and novel features from the highly comparative time-series analysis (HCTSA) package, for the health state estimation of rotating machinery operating under varying conditions. Furthermore, several feature selection methods are investigated to identify features as viable health indicators for the diagnostics and prognostics of technical systems. As a case study, the presented methods are evaluated on real-world and experimentally acquired vibration data of bearings operating under varying speed. The results show that the selected features can successfully be employed as health indicators for technical systems operating under varying conditions.
Keywords: Wind turbine diagnostics; bearing diagnostics; non-stationary operating conditions; varying operating conditions; feature extraction; feature selection; fault detection; failure detection

Rule-based Diagnostics of a Production Line - Aimiyekagbon, Osarenren Kennedy; Muth, Lars; Wohlleben, Meike Claudia; Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
In the industry 4.0 era, there is a growing need to transform unstructured data acquired by a multitude of sources into information and subsequently into knowledge to improve the quality of manufactured products, to boost production, for predictive maintenance, etc. Data-driven approaches, such as machine learning techniques, are typically employed to model the underlying relationship from data. However, an increase in model accuracy with state-of-the-art methods, such as deep convolutional neural networks, results in less interpretability and transparency. Due to the ease of implementation, interpretation and transparency to both domain experts and non-experts, a rule-based method is proposed in this paper, for prognostics and health management (PHM) and specifically for diagnostics. The proposed method utilizes the most relevant sensor signals acquired via feature extraction and selection techniques and expert knowledge. As a case study, the presented method is evaluated on data from a real-world quality control set-up provided by the European prognostics and health management society (PHME) at the conference’s 2021 data challenge. With the proposed method, our team took the third place, capable of successfully diagnosing different fault modes, irrespective of varying conditions.
Keywords: PHME 2021; Feature Selection Classification; Feature Selection Clustering; Interpretable Model; Transparent Model; Industry 4.0; Real-World Diagnostics; Quality Control; Predictive Maintenance

Tire Wear Reduction Based on an Extended Multibody Rear Axle Model - Schütte, Jan; Sextro, Walter (Vehicles)
To analyze the influence of suspension kinematics on tire wear, detailed simulation models are required. In this study, a non-linear, flexible multibody model of a rear axle system is built up in the simulation software MSC Adams/View. The physical model comprises the suspension kinematics, compliance, and dynamics as well as the non-linear behavior of the tire using the FTire model. FTire is chosen because it has a separate tire tread model to compute the contact pressure and friction force distribution in the tire contact patch. To build up the simulation model, a large amount of data is needed. Bushings, spring, and damper characteristics are modeled based on measurements. For the structural components (e.g., control arms), reverse engineering techniques are used. The components are 3D-scanned, reworked, and included as a modal reduced finite element (FE)-model using component mode synthesis by Craig–Bampton. Finally, the suspension model is validated by comparing the simulated kinematic and compliance characteristics to experimental results. To investigate the interaction of suspension kinematics and tire wear, straight line driving events, such as acceleration, driving with constant velocity, and deceleration, are simulated with different setups of wheel suspension kinematics. The influence of the setups on the resulting friction work between tire and road is examined, and an exemplarily calculation of tire wear based on a validated FTire tire model is carried out. The results demonstrate, on the one hand, that the chosen concept of elasto-kinematic axle leads to a relatively good match with experimental results and, on the other hand, that there are significant possibilities to reduce tire wear by adjusting the suspension kinematics.

Identification of joints for a load-adapted shape in a body in white using steady state vehicle simulations - Martin, Sven; Schütte, Jan; Bäumler, C.; Sextro, Walter; Tröster, Thomas (Forces in Mechanics)

Experimental analysis and modelling of bond formation in ultrasonic heavy wire bonding - Schemmel, Reinhard; Scheidemann, Claus; Hemsel, Tobias; Kirsch, Olaf; Sextro, Walter (CIPS 2020; 11th International Conference on Integrated Power Electronics Systems)
Ultrasonic wire bonding is a process to form electrical connections in electronics well established industry. Typically, a clamping tool is pressed on the wire and forced to vibrate at relative high frequency 40 to 100 kHz. The ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes, contamination like oxide layers are removed from the contact zone, the surface roughness is reduced, and with increasing bond duration an metallic connection of wire and substrate is established. It is known that the amount of ultrasonic energy over time directly influences the strength and reliability of the bond connection, but the determination of optimum bond parameters is still a challenging experimental task. For this, in the past different model approaches have been presented, to calculate the bond quality by simulation. Measuring the friction between wire and substrate to validate these models is a challenging task at ultrasonic bonding frequency. Therefore a versatile test rig for bonding experiments at frequencies lower than 1 kHz is setup to get detailed insight into the different phases of the connection process. It includes a piezoelectric force sensor for the measurement of the three-dimensional process forces, an electrodynamic shaker for the vibration excitation and a conventional tension-compression testing machine to apply the bond normal force. Using this test rig, it is possible to observe the different phases of bond formation in detail, validate and enhance existing models and finally optimize bond parameters for different processes.

Schwingungen - Magnus, Kurt; Popp, Karl; Sextro, Walter
Schwingungsprobleme in der Technik analysieren, verstehen und beschreiben Schwingungen treten als nützliche oder auch als störende Erscheinungen fast überall in Natur und Technik auf. Deshalb ist es wichtig, sie zu verstehen, zu deuten oder auch in gewünschter Weise zu beeinflussen. Dieses Lehrbuch gibt eine Einführung in die physikalischen Grundlagen und die mathematische Behandlung von Schwingungen. In der aktuellen Auflage wurden der Text und die Bilder überarbeitet sowie konstruktive Hinweise von Fachkollegen berücksichtigt. Der Inhalt Grundbegriffe und Darstellungsmittel - Freie Schwingungen - Selbsterregte Schwingungen - Parametererregte Schwingungen - Erzwungene Schwingungen - Koppelschwingungen - Kontinuumsschwingungen - Chaotische Bewegungen - Aufgaben und Ergebnisse Die Zielgruppe Studierende der Ingenieurwissenschaften, der Physik und der Mathematik, berufstätige Ingenieure

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (2020 21st International Conference on Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems (EuroSimE))

Evaluation of time series forecasting approaches for the reliable crack length prediction of riveted aluminium plates given insufficient data - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (PHM Society European Conference)
In all fields, the significance of a reliable and accurate predictive model is almost unquantifiable. With deep domain knowledge, models derived from first principles typically outperforms other models in terms of reliability and accuracy. When it may become a cumbersome or an unachievable task to build or validate such models of complex (non-linear) systems, machine learning techniques are employed to build predictive models. However, the accuracy of such techniques is not only dependent on the hyper-parameters of the chosen algorithm, but also on the amount and quality of data. This paper investigates the application of classical time series forecasting approaches for the reliable prognostics of technical systems, where black box machine learning techniques might not successfully be employed given insufficient amount of data and where first principles models are infeasible due to lack of domain specific data. Forecasting by analogy, forecasting by analytical function fitting, an exponential smoothing forecasting method and the long short-term memory (LSTM) are evaluated and compared against the ground truth data. As a case study, the methods are applied to predict future crack lengths of riveted aluminium plates under cyclic loading. The performance of the predictive models is evaluated based on error metrics leading to a proposal of when to apply which forecasting approach.
Keywords: PHM 2019; crack propagation; forecasting; unevenly spaced time series; step ahead prediction; short time series

Model-Based Investigation of the Influence of Wheel Suspension Characteristics on Tire Wear - Schütte, Jan; Sextro, Walter (Lecture Notes in Mechanical Engineering)

Patent EP 3 358 332 B1: Verfahren zur Bestimmung des Beginns einer verschleißbedingten Bauteil-Restnutzungsdauer eines elastisch verformbaren Bauteils, als Strukturteil und/oder Lagerteil eines Geräts. - Reinke, Kai; Bender, Amelie; Meyer, Tobias; Sextro, Walter; Kimotho, James Kuria
Die Erfindung betrifft ein Gerät mit wenigstens einem elastisch verformbaren Bauteil als Strukturteil und/oder Lagerteil, auf das im Betriebsverlauf von wechselnden Betriebszuständen abhängige, unterschiedliche Verformungskräfte einwirken, die zu einem die Bauteilnutzungsdauer begrenzenden Bauteilverschleiß führen, und mit einer Einrichtung zur Bestimmung der Bauteilnutzungsdauer und einer verschleißbedingten Bauteil-Restnutzungsdauer. Erfindungsgemäß wird ein sich zeitversetzt wiederholender, jeweils gleicher Betriebszustand vorbestimmt, dem eine jeweils gleiche Verformungskraft zugeordnet ist, durch die das elastisch verformbare Bauteilmaterial verformt wird. Ein solcher vorbestimmter Betriebszustand wird jeweils von einer Mess- und Auswerteeinheit erkannt und ein Messvorgang durch ein Startsignal selbsttätig gestartet, wobei mit wenigstens einem bauteilzugeordneten Beschleunigungssensor, die aktuelle Beschleunigung der Verformung oder daraus abgeleitete Kennwerte als Kenngröße für eine aktuelle Bauteilsteifigkeit gemessen und jeweils in einer Messkurve gespeichert und verglichen wird.

Integration von Verlässlichkeitsmodellen der Entwicklung in einen Digitalen Zwilling zur Umsetzung einer vorausschauenden Instandhaltung - Kaul, Thorben; Hentze, Julian; Sextro, Walter; Gräßler, Iris (Fachtagung Mechatronik 2019 Paderborn)
In der Entwicklung mechatronischer Systeme spielt die Steigerung der Verlässlichkeit und somit auch der Zuverlässigkeit und der funktionalen Sicherheit eine entscheidende Rolle. Die modellbasierte Entwicklung liefert in Kombination mit unterstützender Software einen wichtigen Beitrag zur Absicherung der Verlässlichkeit mechatronischer Systeme in frühen Entwicklungsphasen. In der Nutzungsphase ermöglichen aktuelle Verfahren der Zustandsüberwachung und moderne Methoden der Regelungstechnik eine effektive Absicherung. Modelle aus der Entwicklung mechatronischer Systeme enthalten weitreichende Informationen über die Architektur, das Verhalten und die Verlässlichkeit eines Systems. Diese Modelle können als Grundlage für die Erstellung eines Digitalen Zwillings für die vorausschauende Instandhaltung verwendet und mit Zustandsdaten des realen Systems kombiniert werden. Die Nutzung der Modelle für den Digitalen Zwilling bietet weitreichende Potenziale und vereinfacht dessen Erzeugung. Die Veröffentlichung beschreibt Rahmenbedingungen der Integration und stellt die Potenziale des Digitalen Zwillings zur vorausschauenden Instandhaltung dar.

Halbachsprüfstand zur kinematischen, elastokinematischen und dynamischen Charakterisierung von Radaufhängungen - Schütte, Jan; Sextro, Walter; Kohl, Sergej (Fachtagung Mechatronik 2019)
Die Achse als einzige Verbindung zwischen Fahrzeugaufbau und Rad hat die Hauptaufgabe das Rad auf der Straße zuführen. Kinematisch betrachtet übernimmt die Radaufhängung, als Teil der Achse, die Funktion, zwischen Rad und Fahrzeugaufbaueinen vertikalen Freiheitsgrad zur Aufnahme von Fahrbahnunebenheiten zu realisieren. Die aus der RadhubundElastokinematik resultierenden Radstellungsänderungen bestimmen dabei maßgeblich die Fahrdynamik. Zur objektivenBeurteilung von Radaufhängungen ist eine genaue Charakterisierung der Radhub- und Elastokinematik erforderlich.Daher wurde zur Identifikation der kinematischen, elastokinematischen und dynamischen Radaufhängungseigenschaftenam Lehrstuhl für Dynamik und Mechatronik der Universität Paderborn ein Halbachsprüfstand entwickelt. Bei der Auslegungwurde Wert auf ein möglichst breites Einsatzspektrum gelegt. Es können verschiedene Typen von Einzelradaufhängungenin Serien- oder Prototypenkonfiguration am Prüfstand analysiert werden. Er ermöglicht eine Identifikation derdynamischen Radstellungsänderungen unter verschiedenen fahrdynamischen Lastfällen und regellosen Anregungen.

Atomization of Fluids with Ultrasound - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter; Sextro, Walter (Conference Proceedings - The 4th Conference on MicroFluidic Handling Systems (MFHS2019))
In a variety of industrial applications, liquids are atomized to produce aerosols for further processing. Example applications are the coating of surfaces with paints, the application of ultra-thin adhesive layers and the atomization of fuels for the production of combustible dispersions. In this publication different atomizing principles (standing-wave, capillary-wave, vibrating-mesh) are examined and discussed. Using an optimized standing-wave system, tough liquids with viscosities of up to about 100 Pas could be successfully atomized.
Keywords: atomization; ultrasound; standing-wave; capillarywave; vibrating-mesh

Messung hochfrequenter In-Plane-Schwingungen mittels Laservibrometrie in räumlich eingeschränkten Umgebungen - Hagedorn, Oliver Ernst Caspar; Pielsticker, Daniel; Hemsel, Tobias; Sextro, Walter (2. VDI-Fachtagung Schwingungen 2019)

Intelligente Herstellung zuverlässiger Kupferbondverbindungen - Sextro, Walter; Brökelmann, Michael
Dieses Buch beschreibt basierend auf dem gleichnamigen Innovationsprojekt im Spitzencluster it’s OWL die Entwicklung intelligenter Verfahren und Systeme, um auch unter variablen Produktionsbedingungen eine zuverlässige Massenfertigung von Kupferbondverbindungen sicherzustellen.Dabei wird der gesamte Prozess der Ultraschall-Verbindungsbildung modelliert. Dies beinhaltet u. a. ein Reibmodell mit gekoppeltem Anbindungsmodell, den Ultraschall-Erweichungseffekt und den Verschleiß des Bondwerkzeugs. Zudem wird das Konzept einer selbstoptimierenden Bondmaschine vorgestellt, welche Prozessparameter in Abhängigkeit von Störgrößen wie Verschleiß anpasst.Das Ultraschallbonden mit Aluminiumdraht ist ein etabliertes Fertigungsverfahren zur Kontaktierung von Leistungshalbleitern. Zukünftige Leistungshalbleiterchips erfordern jedoch einen Technologiewechsel zu Kupferdraht. Die Prozessparameter unterscheiden sich dabei deutlich von den bekannten Aluminiumprozessen, ihre Wechselwirkungen sind weitestgehend unbekannt.
Keywords: Abschlussbericht zum Spitzenclusterprojekt InCuB

Konstruktion und Zustandsüberwachung eines Gummi-Metall-Teils mit integriertem Thermoelement - Bender, Amelie; Reinke, Kai; Sextro, Walter (10. VDI-Fachtagung Schwingungen von Windenergieanlagen 2019)
Gummi-Metall-Teile (GM-Teile) werden zur Schwingungsreduktion u. a. in Windenergieanlagen eingesetzt. Mögliche Anwendungen der Teile liegen in Wellen-, Generator- und Getriebelagerungen, Lagern für die Gondel und ihre Komponenten sowie in Drehmomentstützen. Mit dem Ziel eine prädiktive Instandhaltung zu realisieren, soll eine Zustandsüberwachung für die GM-Teile entwickelt werden. Diese Entwicklung basiert auf der Umsetzung diverser Schritte. Neben der funktionalen Betrachtung wird zwingend auch die konstruktive Integration der Sensoren in das überwachte Teil berücksichtigt. Der Schwerpunkt dieser Arbeit liegt auf der verwendeten Messgröße Temperatur, die mittels ausgewählter Sensorik detektiert wird. Dabei werden Lebensdauerversuche unter instationären Betriebsbedingungen durchgeführt, um diese Messdaten zu generieren. In der Datenauswertung werden sie hinsichtlich der Degradierung des GM-Teils analysiert und für die Ermittlung der nutzbaren Restlebensdauer verwendet. Rubber-metal-elements are used for isolation of vibrations e. g. in wind turbines. Possible applications of the elements are shaft bearings, generator bearings, gearbox bearings, bearings for the nacelle and its components and torque supports. In order to realize predictive maintenance, an accurate condition monitoring system for rubber-metal-elements should be developed. During that development different aspects have to be implemented. Additionally to the functional analysis, the constructive integration of the sensors into the monitored part is mandatory. The focus of this work is on the measured variable temperature, which is detected by means of appropriate sensors. Thereby lifetime tests are run under non-stationary operating conditions to generate temperature measurements. During data analysis, the measured data is analyzed regarding the degradation of the rubber-metal-elements and remaining useful lifetimes are estimated.

Integration von Verlässlichkeitsmodellen der Entwicklung in einen Digitalen Zwilling zur Umsetzung einer vorausschauenden Instandhaltung - Kaul, Thorben; Hentze, Julian; Sextro, Walter; Gräßler, Iris (Fachtagung Mechatronik 2019 Paderborn)
In der Entwicklung mechatronischer Systeme spielt die Steigerung der Verlässlichkeit und somit auch der Zuverlässigkeit und der funktionalen Sicherheit eine entscheidende Rolle. Die modellbasierte Entwicklung liefert in Kombination mit unterstützender Software einen wichtigen Beitrag zur Absicherung der Verlässlichkeit mechatronischer Systeme in frühen Entwicklungsphasen. In der Nutzungsphase ermöglichen aktuelle Verfahren der Zustandsüberwachung und moderne Methoden der Regelungstechnik eine effektive Absicherung. Modelle aus der Entwicklung mechatronischer Systeme enthalten weitreichende Informationen über die Architektur, das Verhalten und die Verlässlichkeit eines Systems. Diese Modelle können als Grundlage für die Erstellung eines Digitalen Zwillings für die vorausschauende Instandhaltung verwendet und mit Zustandsdaten des realen Systems kombiniert werden. Die Nutzung der Modelle für den Digitalen Zwilling bietet weitreichende Potenziale und vereinfacht dessen Erzeugung. Die Veröffentlichung beschreibt Rahmenbedingungen der Integration und stellt die Potenziale des Digitalen Zwillings zur vorausschauenden Instandhaltung dar.

Modellbasierte und experimentelle Charakterisierung von intensiven Ultraschall-Stehwellenfeldern für die Zerstäubung hochviskoser Flüssigkeiten - Dunst, Paul; Hemsel, Tobias; Bornmann, Peter; Littmann, Walter; Sextro, Walter (DAGA 2019)
Für die Zerstäubung hochviskoser Flüssigkeiten werden neben Düsenzerstäubern vor allem UltraschallStehwellenzerstäuber angewendet [1]. Diese ermöglichen ohne weitere Maßnahmen zwar keine gerichtete Zerstäubung, benötigen jedoch im Gegensatz zu Düsenzerstäubern keine hohen Drücke und haben keine hohen Austrittsgeschwindigkeiten. Zur Erzeugung der Ultraschallwellen werden typischerweise piezoelektrische, mit Bolzen verschraubte LangevinWandler verwendet [1-4], die eine starke Schallabstrahlung bei einer elektrischen Eingangsleistung von bis zu einigen Kilowatt erzeugen können. Wie bei jedem anderen schwingenden System emittiert der Ultraschallwandler zunächst eine Wanderwelle. Mit einem Reflektor, der gegenüber der Sonotrode angeordnet ist, wird eine stehende Welle erzeugt. Im Resonanzabstand zwischen Reflektor und Wandler werden abgestrahlte und reflektierte Wellen so überlagert, dass höhere Schalldruckamplituden erzielt werden. Ein einfacher Ansatz zur Maximierung des Schallpegels im Stehwellenfeld ist die Erhöhung der Schwingungsamplituden des Wandlers, die jedoch zu Schäden oder zumindest zu einer Verringerung der Lebensdauer führen kann. Hohe Schalldrücke werden auch bei geringen Abständen zwischen Wandler und Reflektor erreicht. Das Volumen des Schallfeldes ist in diesem Fall jedoch für die meisten Prozesse zu klein. Ein weiterer Ansatz ist die Verwendung zweier entgegengesetzt angeordneter Wandler [5]. In diesem Fall erfordert jedoch die Erzeugung einer stehenden Welle eine genaue Abstimmung von Frequenz und Phase beider Wandler, was eine komplexe Steuerung erfordert. Ebenso ist es möglich, geometrische Randbedingungen des Stehwellensystems zu optimieren, sodass es zu optimaler Interferenz der Wellen kommt. Im Folgenden wird der Anschaulichkeit halber vereinfachend angenommen, dass der Wandler an seiner Sonotrodenoberfläche einzelne Schallstrahlen aussendet, die in Nähe des Wandlers nahezu parallel verlaufen und sich mit zunehmender Entfernung vom Wandler auffächern. Ein einfaches Stehwellensystem, bestehend aus ebener Sonotrode und ebenem Reflektor, erzeugt bei kleinem Abstand zwischen Sonotrode und Reflektor sehr hohe Schallpegel, da nahezu sämtliche ausgesandten Schallstrahlen in Richtung der Sonotrode reflektiert werden positive Interferenz entsteht. Erhöht man jedoch den Abstand zwischen Sonotrode und Reflektor, so nehmen die Verluste durch Schallstrahlen, die den Prozessraum verlassen, zu. Wie Abbildung 1 gezeigt, werden nur Schallstrahlen, die in etwa parallel zur Rotationsachse verlaufen, zum Wandler zurück reflektiert und tragen zum Stehwellenfeld bei. Die Strahlen haben zudem abhängig vom Abstrahlwinkel unterschiedliche Weglängen. Die Stehwellenbedingung ist demnach nur für Strahlen in der Nähe der Rotationsachse exakt erfüllt. Um dies zu vermeiden, müssen die Geometrien von Wandler und Reflektor optimiert werden. In den folgenden Abschnitten wird zunächst ein Optimierungsansatz vorgestellt. Mithilfe eines FiniteElemente-Modells werden die Auswirkungen einer optimierten Geometrie auf den maximalen Schalldruckpegel untersucht. Ergebnisse werden durch Messungen an einem experimentellen Aufbau eines Stehwellensystems validiert. Es wird gezeigt, wie sich die Optimierung der geometrischen Randbedingungen auf die Zerstäubung hochviskoser Flüssigkeiten auswirkt.

Using complex multi-dimensional vibration trajectories in ultrasonic bonding and welding - Schemmel, Reinhard; Hemsel, Tobias; Dymel, Collin; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (Sensors and Actuators A: Physical)
Ultrasonic joining is a common industrial process. In the electronics industry it is used to form electrical connections, including those of dissimilar materials. Multiple influencing factors in ultrasonic joining are known and extensively investigated; process parameters like ultrasonic power, bond force, and bonding frequency of the ultrasonic vibration are known to have a high impact on a reliable joining process and need to be adapted for each new application with different geometry or materials. This contribution is focused on increasing ultrasonic power transmitted to the interface and keeping mechanical stresses during ultrasonic bonding low by using a multi-dimensional ultrasonic transducer concept. Bonding results for a new designed connector pin in IGBT-modules achieved by multi- and one-dimensional bonding are discussed.
Keywords: Ultrasonic bonding; Ultrasonic welding; Multi-dimensional bonding; Complex vibration; Multi-frequent; Two-dimensional friction model

Remaining useful lifetime prediction based on adaptive failure thresholds - Bender, Amelie; Schinke, Lennart; Sextro, Walter (Proceedings of the 29th European Safety and Reliability Conference (ESREL2019))
Remaining useful lifetime (RUL) predictions as part of a condition monitoring system are focused in more and more research and industrial applications. To establish an efficient and precise estimate of the RUL of a technical product, different uncertainties have to be handled. To minimize the uncertainties of the RUL estimation, a reliable and accurate prognostic approach as well as a good failure threshold are important. Regarding the failure threshold, most often an expert sets a fixed failure threshold. However, neither the a priori known failure threshold nor a fixedthreshold value are feasible in every application. Especially in the case of varying characteristics of the monitored system, an adaptive failure threshold is of great importance concerning the accuracy of the RUL estimation. Rubber-metal-elements, which are used in a wide range of applications for vibration and sound isolation, are mon-itored by thermocouples to allow for lifetime predictions. Therefore, the element’s state is described by its temper-ature during its service life. Aiming to establish accurate RUL predictions of a rubber-metal-element, uncertainties due to nonlinear material characteristics and changing operational conditions have to be considered. Consequently, different temperature-based failure threshold definitions are implemented and compared within a particle filtering approach.
Keywords: RUL prediction; adaptive threshold; prognostics; condition monitoring

Digital Twin for Reliability Analysis During Design and Operation of Mechatronic Systems - Kaul, Thorben; Bender, Amelie; Sextro, Walter (Proceedings of the 29th European Safety and Reliability Conference (ESREL2019))
As the emerging digitalization of technical systems offers immense opportunities to be exploited by means of bigdata analysis, ubiquitous computing and largely networked systems, the digital twin comes into focus to combineall these aspects to an attendant model of an individual system during design phase as well as during operation.Since state-of-art technical systems are growing increasingly complex due to inherent intelligence and increasingfunctionality, i. e. autonomous behavior so far, it becomes considerably challenging to ensure reliability for thosesystems. Many methods were developed to support a reliability focused design or reliability-by-design approachesto tackle this challenge during design process. In field, data-based methods, i. e. condition monitoring enabled bythe rise of machine learning approaches, are exploited to ensure a reliable operation based on the current conditionof the monitored system. In order to take advantage of existing models of system reliability during design phaseand condition monitoring systems during operation, a method is proposed to combine both approaches in order toset up a digital twin with focus on system reliability. The base model of the digital twin is taken from the systemreliability model from the design phase and is used during operation and therein updated to the current reliabilitybased on the state estimation of the condition monitoring system. The approach is illustrated with a case study of arolling bearing test rig.

A particle filtering approach for temperature based prognostics - Bender, Amelie; Sextro, Walter (Safety and Reliability – Safe Societies in a Changing World)
Rubber-metal-elements are used in a wide range of applications for vibration and sound isola- tion. Nowadays it is state of the art to calculate the lifetimes of these elements under mechanical stress prior to their service life. To establish more reliable and safer rubber-metal-elements, continuous monitoring by dif- ferent sensors can be used. Especially prognostics enable a rise in reliability, availability and safety. To estab- lish these advantages, estimating the remaining useful lifetime of rubber-metal-elements should be realized during its service life based on current information on its condition. Therefore a suitable measure to monitor the condition of the element is necessary. This work focuses on temperature signals. This approach allows in- cluding the ambient temperature and thereby involving changing operating conditions. For estimating the RUL of rubber-metal-elements a model-based prognostics approach based on particle filtering is proposed. Its performance is analyzed regarding relevant parameters to enable the best performance for the applied data.

Vibration Assisted Dosing, Mixing and Transport of Dry Fine Powders - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter.; Sextro, Walter (ACTUATOR 2018; 16th International Conference on New Actuators)
The handling of fine powders is an important task in modern production processes. However, as fine powders strongly tend to adhesion and agglomeration, their processing with conventional methods is difficult or impossible. Especially when processing small amounts of highly sensitive fine powders, conventional methods reach their technical limits. In process steps such as dosing, transport, and especially mixing of fine powders new methods are required. Apart from the well-known method of manipulating powder properties by adding chemical additives, this contribution aims at improving the handling of dry fine powders by using vibrations at different frequencies. Modules are presented, which enable the continuous dosing, the homogeneous mixing and the transport of dry fine powders. Finally, these modules are combined for the production of a homogeneous mixture of two dry fine powders.

Vibration-Assisted Handling of Dry Fine Powders - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Sextro, Walter (Actuators 2018, 7(2).)
Abstract:Since ﬁne powders tend strongly to adhesion and agglomeration, their processing withconventional methods is difﬁcult or impossible. Typically, in order to enable the handling of ﬁnepowders, chemicals are added to increase the ﬂowability and reduce adhesion. This contributionshows that instead of additives also vibrations can be used to increase the ﬂowability, to reduceadhesion and cohesion, and thus to enable or improve processes such as precision dosing, mixing,and transport of very ﬁne powders. The methods for manipulating powder properties are describedin detail and prototypes for experimental studies are presented. It is shown that the handling of ﬁnepowders can be improved by using low-frequency, high-frequency or a combination of low- andhigh-frequency vibration.
Keywords: powder handling; ﬂowability; dosing; transport; mixing; dispersion; piezoelectricactuators; vibrations

Numerical and statistical investigation of weld formation in a novel two-dimensional copper-copper bonding process - Dymel, Collin; Eichwald, Paul; Schemmel, Reinhard; Hemsel, Tobias; Brökelmann, Michael; Hunstig, Matthias; Sextro, Walter ((Proceedings of 7th Electronics System-Integration Technology Conference, Dresden, Germany))
State-of-the-art industrial compact high power electronic packages require copper-copper interconnections with larger cross sections made by ultrasonic bonding. In comparison to aluminium-copper, copper-copper interconnections require increased normal forces and ultrasonic power, which might lead to substrate damage due to increased mechanical stresses. One option to raise friction energy without increasing vibration amplitude between wire and substrate or bonding force is the use of two-dimensional vibration. The first part of this contribution reports on the development of a novel bonding system that executes two-dimensional vibrations of a tool-tip to bond a nail- like pin onto a copper substrate. Since intermetallic bonds only form properly when surfaces are clean, oxide free and activated, the geometries of tool-tip and pin were optimised using finite element analysis. To maximize the area of the bonded annulus the distribution of normal pressure was optimized by varying the convexity of the bottom side of the pin. Second, a statistical model obtained from an experimental parameter study shows the influence of different bonding parameters on the bond result. To find bonding parameters with the minimum number of tests, the experiments have been planned using a D-optimal experimental design approach.
Keywords: ultrasonic wire-bonding; bond-tool design; parameter identification; statistical engineering

Experimental investigations on the impact of bond process parameters in two-dimensional ultrasonic copper bonding - Dymel, Collin; Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias ((Proceedings of 8th Electronics IEEE CPMT Symposium Japan (ICSJ 2018), Kyoto, Japan))
Ultrasonic bonding and welding are common friction based approaches in the assembly of power electronics. Interconnections with cross-sections of 0.3 mm² up to 12 mm² made from copper are well suited in high power applications. For increasing friction energy, which is responsible for bond formation, a two-dimensional vibration approach is applied to newly developed interconnection pins. Using two-dimensional vibration for bonding requires identification of suitable bonding parameters. Even though simulation models of wire bonding processes exist, parameters for the two-dimensional pin-bonding process cannot be derived accurately yet. Within this contribution, a methodology and workflow for experimental studies identifying a suitable bond parameter space are presented. The results of a pre-study are used to set up an extensive statistical parameter study, which gives insights about the bond strength change due to bond process parameter variation. By evaluation of electrical data captured during bonding, errors biasing the resulting shear forces are identified. All data obtained during the experimental study is used to build a statistical regression model suitable for predicting shear forces. The accuracy of the regression model’s predictions is determined and the applicability to predict process parameters or validate simulation models is assessed. Finally, the influence of the tool trajectory on the bond formation is determined, comparing one dimensional, elliptic and circular trajectories.
Keywords: ultrasonic two-dimensional bonding; electrical interconnection; process parameters

Steigerung der Intelligenz mechatronischer Systeme - Meyer, Tobias; Kaul, Thorben; Kimotho, James Kuria; Sextro, Walter
Selbstoptimierung bietet die Möglichkeit der autonomen Anpassung des Systemverhaltens an veränderliche Ziele. Dabei ist vor allem der Aspekt Zuverlässigkeit von maßgeblicher Bedeutung, da über einen an die aktuelle Systemzuverlässigkeit angepassten Betriebspunkt die Leistungsfähigkeit verbessert wird, während das Ausfallverhalten besser vorhersehbar wird. Zur Anpassung des Systemverhaltens an die aktuelle Zuverlässigkeit mittels Selbstoptimierung müssen die ersten beiden Schritte des Selbstoptimierungsprozesses unterstützt werden. Für die Analyse der Ist-Situation ist eine Erkennung des aktuellen Degradationszustands mittels Condition Monitoring notwendig. Zur Auswahl geeigneter Verfahren werden bestehende Ansätze hinsichtlich ihrer Eignung klassifiziert. Der zweite Schritt, die Bestimmung der Systemziele, wird durch eine strukturierte Methode zum Finden verlässlichkeitsrelevanter Zielfunktionen ergänzt. Dabei werden kritische Komponenten identifiziert, Optimierungsparameter festgelegt und die Verlässlichkeit in Abhängigkeit des Systemverhaltens quantifiziert. Entwickler selbstoptimierender Systeme werden somit durch geeignete Mittel bei der Implementierung beider Schritte unterstützt. Abschließend wird der praktische Einsatz der vorgestellten Methoden anhand zweier Beispiele gezeigt.

Effects of different working frequencies on the joint formation in copper wire bonding - Schemmel, Reinhard; Althoff, Simon; Sextro, Walter; Unger, Andreas; Brökelmann, Michael; Hunstig, Matthias (CIPS 2018 - 10th International Conference on Integrated Power Electronics Systems (CIPS 2018))
Ultrasonic wire bonding is used to connect the electrical terminals of semiconductor modules in power electronics. Mul- tiple inﬂuencing factors in wedge/wedge bonding are known and extensively investigated. A constructively settable but rarely examined parameter is the bonding frequency. In case of bonding on challenging substrates, e.g. supple substruc- tures, a high inﬂuence of the working frequency is observed. The choice of the working frequency is typically based on experimental investigations for a certain component or substrate and needs to be evaluated anew for new applications. A profound understanding of the inﬂuence of the working frequency is required to achieve a reliable bond process and a short process development. Here a generalized model for the numerical simulation of the bond formation with respect to the dynamics of the substructure is presented. The simulation results are compared to experiments using 300 µm copper wire at different working frequencies and geometries of the substructure.

Numerical and experimental investigations in ultrasonic heavy wire bonding - Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter (6th European Conference on Computational Mechanics (ECCM 6))
Ultrasonic wedge/wedge-wire bonding is used to connect electrical terminals of semiconductor modules in power electronics. The wire is clamped with a tool by a normal force and ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes contaminations like oxide layers are removed from the contact zone and the surface roughness is reduced, thus the real contact area is increased. In the next step of bond formation, thermomechanical forces create micro-junctions between the wire and substrate and the bond strength increases. The bond parameters like the bond normal force, the ultrasonic vibration amplitude and the geometry of the clamping tool show a high influence on the strength and reliability of the wire bond and need to be investigated in detail. Therefore, in this contribution the dynamical behaviour of the ultrasonic system, the wire and the substrate are modeled in form of substructures, which are connected by the friction contacts between tool and wire and between wire and substrate. Approaches for modelling the time variant contact behaviour, the substrate dynamics, and the model order reduction for a time efficient simulation are described to simulate the full bonding process.

Intelligent Production of Wire Bonds using Multi-Objective Optimization – Insights, Opportunities and Challenges - Unger, Andreas; Hunstig, Matthias; Meyer, Tobias; Brökelmann, Michael; Sextro, Walter (In Proceedings of IMAPS 2018 – 51st Symposium on Microelectronics, Pasadena, CA, 2018)
Ultrasonic wire bonding is an indispensable process in the industrial manufacturing of semiconductor devices. Copper wire is increasingly replacing the well-established aluminium wire because of its superior electrical, thermal and mechanical properties. Copper wire processes differ significantly from aluminium processes and are more sensitive to disturbances, which reduces the range of parameter values suitable for a stable process. Disturbances can be compensated by an adaption of process parameters, but finding suitable parameters manually is difficult and time-consuming. This paper presents a physical model of the ultrasonic wire bonding process including the friction contact between tool and wire. This model yields novel insights into the process. A prototype of a multi-objective optimizing bonding machine (MOBM) is presented. It uses multi-objective optimization, based on the complete process model, to automatically select the best operating point as a compromise of concurrent objectives.
Keywords: wire bonding; multi-objective optimization; process model; copper wire; self-optimization

Integrated modeling of behavior and reliability in system development - Hentze, Julian; Kaul, Thorben; Gräßler, Iris; Sextro, Walter (ICED17, 21ST INTERNATIONAL CONFERENCE ON ENGINEERING DESIGN, Nr. DS 87-USB)

Entwicklung eines Condition Monitoring Systems für Gummi-Metall-Elemente - Bender, Amelie; Kaul, Thorben; Sextro, Walter (Verlagsschriftenreihe des Heinz Nixdorf Instituts Band 369, Paderborn, 2017)
Zuverlässigkeit, Sicherheit und Verfügbarkeit gewinnen bei der Anwendung von technischen Systemen eine immer größere Bedeutung. Aus diesem Grund hat sich Condition Monitoring, die Zustandsüberwachung eines technischen Produkts, in verschiedenen Industriebranchen etabliert. Die sensorbasierte Überwachung eines Produkts während seiner Betriebsdauer in Kombination mit Condition Monitoring Methoden ermöglichen die Bestimmung des aktuellen Zustands des Produkts und somit eine Diagnose, ob das Produkt seine ihm zugeschriebene Funktion zum aktuellen Zeitpunkt erfüllt. Neben Diagnosen bietet Condition Monitoring auch die Möglichkeit Prognosen aufzustellen, dabei wird die restliche Nutzungsdauer des Produkts aufbauend auf geeigneten Sensordaten geschätzt. So kann eine intelligente Wartungsplanung umgesetzt werden, die im Gegensatz zu klassischen Ansätzen keine festen Wartungsintervalle benötigt und die Nachteile einer rein reaktiven Wartung kompensiert. Stattdessen ist es möglich ein Element bis vor das Ende seiner Lebensdauer zu nutzen und erst dann zu warten, um eine optimale Nutzung zu gewährleisten. Durch eine Bestimmung der verbleibenden Restlebensdauer während des Betriebs ist eine optimale Wartungsplanung möglich, wodurch die Verfügbarkeit und die Auslastung der überwachten Produkte signifikant gesteigert werden kann. In dieser Arbeit soll ein produktspezifisches Condition Monitoring System für Gummi-Metall-Elemente entwickelt werden. Diese Elemente werden zur Federung, Geräusch- und/oder Schwingungsisolation in vielen verschiedenen Anwendungen eingesetzt, wie bspw. in Nutz- und Schienenfahrzeugen oder Windenergieanlagen. In Industrie und Forschung werden bereits Zustandsüberwachungen von Systemen mit integrierten Gummi-Metall-Elementen eingesetzt, allerdings noch keine Condition Monitoring Systeme zur alleinigen Zustandsüberwachung dieser Elemente. Aktuell ist es üblich die Lebensdauer dieser Elemente aufbauend auf beschleunigten Lebensdauerversuchen und Erfahrungswerten abzuschätzen. Mit dem Ziel die Lebensdauer des fokussierten Produkts präziser vorherzusagen und damit eine intelligente Wartungsplanung zu ermöglichen, wird die Entwicklung eines Condition Monitoring Systems für Gummi-Metall-Elemente angestrebt und in dieser Arbeit erläutert.
Keywords: Zustandsüberwachung; Condition Monitoring; Prognose; Gummi-Metall-Elemente; Restlebensdauerschätzung

Modellbasierte Prognose der nutzbaren Restlebensdauer von Gummi-Metall-Elementen - Bender, Amelie; Kimotho, James Kuria; Kohl, Sergej; Sextro, Walter; Reinke, Kai (15. Internationale Schienenfahrzeugtagung)
In vielen verschiedenen Industriezweigen hat sich Condition Monitoring aufgrund seiner finanziellen und sicherheitstechnischen Vorteile bereits etabliert. Um die Verlässlichkeit und die Auslastung zu steigern, sowie um die Lebenszykluskosten zu reduzieren, steigt auch im Schienenfahrzeugbereich die Anzahl an eingesetzten Condition Monitoring Systemen. Studien zu Versagensmodi von Schienenfahrzeugen haben gezeigt, dass Versagensursachen meistens in den Radprofilen oder im Fahrwerk liegen [1]. Wird das Fahrwerk heute mittels Condition Monitoring überwacht, werden hierfür häufig Sensoren an den Wagons angebracht, um bspw. deren Schwingungen zu kontrollieren [2, 3]. In dieser Arbeit liegt der Fokus auf Gummi-Metall-Elementen (GM-Elementen) der Jörn GmbH.; als elastische Lager im Drehgestell sind diese Teil des Fahrwerks eines Schienenfahrzeugs. Mit dem Ziel die Wartungsplanung dieser Elemente zu optimieren, ist untersucht worden, ob diese Elemente einzeln mittels Condition Monitoring überwacht werden können. Die hierfür durchgeführten beschleunigten Lebensdauertests werden im nächsten Abschnitt erläutert. Anschließend werden die modellbasierten Methoden dargestellt, die aufbauend auf den im Versuch aufgezeichneten Daten eine Prognose der nutzbaren Restlebensdauer (RUL, remaining useful lifetime) der GM-Elemente aufstellen. Im letzten Abschnitt folgen eine kurze Zusammenfassung und ein Ausblick.